2018
DOI: 10.3802/jgo.2018.29.e49
|View full text |Cite
|
Sign up to set email alerts
|

Value of combined adjuvant chemotherapy and radiation on survival for stage III uterine cancer: is less radiation equal to more?

Abstract: ObjectiveLocally advanced endometrioid adenocarcinoma (LA-EAC) accounts for the majority of deaths for this cancer, yet there is no consensus on adjuvant treatment after surgery. Past studies suggest that combined modality treatment (CMT) may improve outcomes over treatment with chemotherapy (CT) or radiation therapy (RT, either external beam radiotherapy [EBRT] or vaginal brachytherapy [VBT]) alone. Using a large US-based population-based registry, we evaluated adjuvant CMT in LA-EAC and the relative benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…While chemotherapy use became more common, many women were treated with chemotherapy in combination with radiation, with several studies suggesting a possible trend towards improved survival among these women. 17,18,19,20 In our cohort, use of chemotherapy, with or without brachytherapy, was slightly more common than use of combination therapy.…”
Section: Discussionmentioning
confidence: 63%
“…While chemotherapy use became more common, many women were treated with chemotherapy in combination with radiation, with several studies suggesting a possible trend towards improved survival among these women. 17,18,19,20 In our cohort, use of chemotherapy, with or without brachytherapy, was slightly more common than use of combination therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Several published data suggest that patients with stage III endometrial cancer might benefit from a combination radiotherapy-chemotherapy approach. According to Wang et al [3], who analyzed 8738 patients from the United States' National Cancer Database with (surgically staged) stage III uterine cancer who had received adjuvant treatments, concluded that chemoradiotherapy was associated with superior survival outcomes compared to monotherapy. Studies by Kuku et al [4], Marchetti et al [5], and Lee et al [27] of 90, 82, and 66 patients with stage IIIC endometrioid adenocarcinoma, respectively, all concluded that sequential chemoradiotherapy improved patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer is the most common malignancy of the female genital tract; moreover, its incidence rate continues to increase [1]. Approximately one-fifth of the patients are diagnosed at an already advanced stage; the 5-year overall survival (OS) rates of those with stage III disease who are able to undergo optimal resection are 70-80% when adjuvant therapy is administered and 30-40% when it is not [2,3]. The most suitable adjuvant treatment for stage III endometrial cancer remains undefined, including the appropriate adjuvant chemotherapy, radiotherapy, or combined chemoradiotherapy options [4][5][6][7]; notably, only a few prospective studies on this topic have been performed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Three previously published randomized trials compared adjuvant chemotherapy with radiotherapy and found no difference in overall survival and progression-free survival ( 34 36 ). Since pelvic relapse has been reported frequently in patients who had undergone chemotherapy alone ( 37 , 38 ), the combination of radiotherapy and chemotherapy was proposed to maximize both local and distant control ( 39 , 40 ). The updated analysis of the Postoperative Radiation Therapy in Endometrial Carcinoma 3 has exhibited significantly improved overall survival and failure-free survival in stage III patients treated with chemoradiotherapy vs. radiotherapy alone ( 41 ).…”
Section: Discussionmentioning
confidence: 99%